Carbon nanotube electrodes for effective interfacing with retinal tissue - Shoval, Asaf; Adams, Christopher; David-Pur, Moshe; Shein, MArk; Hanein, Yael; Sernagor, Evelyne (Frontiers in Neuroengineering, 2009)
We have investigated the use of carbon nanotube microelectrodes as an interface material for retinal recording and stimulation applications. Test devices were micro-fabricated and consisted of 60 pristine 30 um electrodes coated with chemical vapor deposited carbon nanotubes, resulting in conducting, three dimensional surfaces with a high effective interfacial area. These attributes are important both for the quality of the cell-surface coupling as well as for electro-chemical interfacing efficiency. The entire chip was packaged to fit a commercial multielectrode recording and stimulation system. Electrical recordings of spontaneous spikes from whole-mount neonatal mouse retinas were consistently obtained minutes after retinas were placed over the electrodes, exhibiting typical bursting and propagating waves. Most importantly, the signals obtained with carbon nanotube electrodes have exceptionally high signal to noise ratio, reaching values as high as 75. Moreover, spikes are marked by a conspicuous gradual increase in amplitude recorded over a period of minutes to hours, suggesting improvement in cell-electrode coupling. This phenomenon is not observed in conventional commercial electrodes. Electrical stimulation using carbon nanotube electrodes was also achieved. We attribute the superior performances of the carbon nanotube electrodes to their three dimensional nature and the strong neuro-carbon nanotube affinity. The results presented here show the great potential of carbon nanotube electrodes for retinal interfacing applications. Specifically, our results demonstrate a route to achieve a reduction in the electrode size down to few micrometers in order to achieve high efficacy local stimulation needed in retinal prosthetic devices.